RESEPSI MASYARAKAT JAWA TERHADAP HADIS MENGUSAP KEPALA ANAK YATIM PADA MALAM ASYURA DITINJAU DARI TAFSIR MAQASHIDI - Shiyama, Ama; Moh. Abdul Azis Sahlan (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2026)
This article examines the Javanese community’s reception of the hadith concerning the recommendation to stroke the head of an orphan on the night of ‘Āshūrā through the perspective of maqāṣid-based interpretation (tafsir maqāṣidī). The month of Muharram, known in Javanese tradition as Sura, is understood not only as a sacred month in Islam but also as a symbolic space rich in cultural meaning and local spirituality. This study aims to analyze the transformation of the meaning of the night of ‘Āshūrā within Javanese tradition and to explore the values of social concern for orphans derived from the Prophet Muhammad’s hadith. The research employs a qualitative method with a library research approach, using descriptive-analytical analysis of hadith compilations, classical and contemporary Qur’anic commentaries, and literature on Islamic–Javanese culture. The findings indicate that although the hadith on stroking the head of an orphan is classified as gharīb, it possesses strong substantive legitimacy and is consistent with the universal Islamic principles of compassion and protection for vulnerable groups. From a maqāṣidī perspective, this hadith reflects the objectives of Islamic law, namely the protection of life (ḥifẓ al-nafs), lineage (ḥifẓ al-nasl), and social welfare (ḥifẓ al-māl). Javanese cultural practices, such as orphan charity and the wilujengan Sura ritual, demonstrate the internalization of these maqāṣidī values in the form of social solidarity and contextual collective piety.